Reformulation of the domain-level semantic pattern of axiological evaluation in the lexicon of English verbs - Lago, Ángel Felices (HERMES - Journal of Language and Communication in Business, 2003)
The three-level hierarchy of values in Faber and Mairal‘s work (Constructing a Lexicon of English Verbs, Berlin: Mouton de Gruyter, 1999) is based on the scales of values given by Max Scheler or Józef Tischner, which are deeply rooted in the theory of the Great Chain of Being (employed by Aristotle in his scala naturae). Faber and Mairal also provide an account of the relationship between lexical structure and cognition. A key issue was the introduction of a cognitive axis and a typology of predicate schemas in the lexicon (at lexeme, sub-domain and domain level). Among the four domain-level semantic patterns proposed, axiology is considered to appear in many domains. How-ever, in this article it is claimed that the axiological parameter needs further clarification and decomposition. Its structure is multidimensional, internally hierarchical and ca-nonical. In consequence, the three-level hierarchy of values in the lexicon of English verbs is reformulated and the axiological parameter is divided into multilevel categories crossed by two layers of canonical axes. It is also claimed that the axiological formula incorporating this might improve the understanding of this parameter within the lexical architecture of the verbal lexicon.